A Study On English Teaching Techniques On Reading SkillBy Teacher To Promote Students' Participation Of The Eighth Grade Students At SMP N 2 Sawit In 2012/2013 Academic Year - Rahayu, Heni Fitri, Drs. Djoko Srijono, M.Hum, Siti Fatimah, S.Pd, M.Hum (2013)
This research is aimed at describing: 1) teaching reading techniques used by English teacher in the classroom activities, 2) the teacher's roles in the classroom activities, 3) the students' role in the classroom activities, and 4) the teaching reading techniques to promote the students' participation. This research is descriptive research which the data are obtained from elements that are related of teaching-learning process. The method of collecting data is conducted by doing observation, analyzing data, and conducting interview. There are five points have been found in this research, namely the technique for teaching reading, the process of teaching reading, teacher's role, student's role, and the problem faced by teacher. The result of this research indicates that there are two techniques which promote students' participation; reading aloud and pattern drill. Besides, there is technique which does not promote students' participation; silent reading. In the classroom activities, the teacher has roles as a facilitator who facilitates the teaching-learning process, as an organizer who organizes the condition of the classroom, as a counselor who helps the students to solve the difficulties, and a guide who handles teachinglearning process, while in the classroom activities, the students have roles as a communicator who communicate with other students in discussing the difficulties, and as a planner who is responsible to their achievement.